2009
DOI: 10.1111/j.1399-5618.2009.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Similar immune profile in bipolar disorder and schizophrenia: selective increase in soluble tumor necrosis factor receptor I and von Willebrand factor

Abstract: The present results indicate specific alterations of endothelium-related inflammation processes in both bipolar disorder and schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 70 publications
(81 reference statements)
3
83
2
4
Order By: Relevance
“…Recent researches focusing on inflammation found that depressive and manic states are associated with increased peripheral levels of pro-inflammatory cytokines, such as interleukin (IL)-2, IL-6, IL-8 and tumour necrosis factor (TNF)-α [57][58][59] and of TNF receptor 1 compared to controls [60]. Moreover, a specific profile of mRNA expression for inflammatory genes was found in bipolar subjects [61].…”
Section: Sleep and Inflammationmentioning
confidence: 97%
“…Recent researches focusing on inflammation found that depressive and manic states are associated with increased peripheral levels of pro-inflammatory cytokines, such as interleukin (IL)-2, IL-6, IL-8 and tumour necrosis factor (TNF)-α [57][58][59] and of TNF receptor 1 compared to controls [60]. Moreover, a specific profile of mRNA expression for inflammatory genes was found in bipolar subjects [61].…”
Section: Sleep and Inflammationmentioning
confidence: 97%
“…Inflammation is recognised as an integral component of both metabolic syndrome and psychiatric disorders (Hope 2009;Na 2012), with high serum levels of C-reactive protein (CRP) and proinflammatory cytokines such as interleukin IL-6 and tumour necrosis factoralpha (TNF-α) in both conditions. Genetic factors such as the presence of specific genes responsible for a predisposition to metabolic problems and variations in the leptin-melanocortin pathway that contribute to heterogeneity in antipsychoticinduced weight gain are also important causes of metabolic syndrome.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…This leads to inflammation, which ultimately confers higher risks of atherosclerosis and coronary artery disease. Blood serum levels of CRP, TNF-α and homocysteine have been found to be increased in patients with schizophrenia (Hope 2009). C-reactive protein was found to have a positive association with waist circumference and diastolic blood pressure, while homocysteine has a positive association with waist circumference, systolic and diastolic blood pressure, triglycerides and glucose (Vuksan-Cusa 2012).…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…The possible biomarkers of mood disorder and schizophrenia in the literature, including neurotrophic factors, circulating immunological parameters, thyroid hormones, neuropeptides, and oxidative stress markers, are limited by their specificity to each disorder (45). Most schizophrenic patients in this study were not classified as BD sample by the BD-A committee on the focus array.…”
Section: Discussionmentioning
confidence: 99%